IMPLEMENTATION OF GROUP INVESTIGATION LEARNING MODEL TO IMPROVE PROBLEM SOLVING ABILITY IN CLASS VIII SMP NEGERI 11 MEDAN - Leni . Anggraini; KMS M Amin Fauzi (Universitas Negeri Medan, 2017)
ABSTRACTThe purpose of this study was to: 1) Repairing the learning process by using the group investigation learning model to improve the problem solving ability. 2) To know the big of the improvement of students' problem solving ability using Group Investigation learning model. 3) To know the process of students’ answer in improving the problem solving ability. Type of this research is the Classroom Action Research (CAR). This research was conducted at SMP Negeri 11Medan academic year 2014/2015. The population of this research was all students at SMP Negeri 11 Medan in grade VIII-7. This study consisted of two cycles, the first cycle consists of two meetings and the second cycle consists of two meetings. The results of this study could be seen: (1) The process of implementation problem based learning was running well because the observation of implementation based teacher side is good category and student side is active category. (2) The improvement of problem solving ability of students by the implementation of group investigation learning model belongs to high category with the normalized gain value is 0.83 where the average of problem solving ability of students in cycle I is 48.16 and in cycle II the average is improved become 91.02. (3) The process of students’ answer is improve from the cycle 1 to cycle II. There are 80% of students to meet the minimum completeness criteria after learning activities using group investigation learning model in small study groups.Keywords: Problem Solving Ability, Group InvestigationABSTRAKTujuan penelitian ini adalah: 1) Untuk memperbaiki proses pembelajaran dengan menggunaka model pembelajaran group investigasi untuk meningkatkan kemampuan pemecahan masalah. 2) Untuk mengetahui seberapa besar peningkatan kemampuan pemecahan masalah dengan menggunakan model pembelajaran group investigasi. 3) Untuk mengetahui proses jawaban siswa dalam peningkatan kemampuan pemecahan masalah. Tipe penelitian ini adalah penelitian Tindakan Kelas (PTK). Penelitian ini dilaksanakan di SMP Negeri 11 Medan tahun ajaran 2014/2015. Populasi dalam penelitian ini adalah semua siswa di SMP Negeri 11 Medan di kelas VIII-7. Penelitian ini dilakukan sebanyak dua siklus, siklus pertama terdiri dari dua pertemuan, dan siklus kedua dilakukan sebanyak dua pertemuan. Hasil penelitian ini dapat dilikat sebagai berikut: (1) proses penerapan model pembelajaran group investigasi berlangsung dengan baik karena observasi yang dilakukan dari sisi guru dikategorikan baik dan dari sisi siswa diaktegorikan aktif. (2) Peningkatan kemampuan pemecahan masalah siswa dengan menggunakan model pembelajaran group investigasi dikategorikan tinggi dengan normalisasi gain 0.83 dimana rata-rata kemampuan pemecahan masalah siswa pada siklus 1 48.16 dan siklus II 91.02. (3) Proses jawaban siswa meningkat dari siklus I ke siklus II. Ada lebih dari 80% siswa melewati nilai ketuntasan setelah menggunakan model pembelajaran group investigasi dalam kelompok kecil.Keywords: Kemampuan Pemecahan Masalah, Grup Investigasi